Deliberative CSR: Alternative CSR Concept based on Liberation Theology Perspective - Astri Dyastiarini; Gugus Irianto; Roekhudin Roekhudin (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2021)
Theories underlying the CSR concept only takes side of secular world because it is based on materialistic world view which directs CSR practice at pragmatic goals. Therefore, CSR needs conceptual development which is able to balance material and spiritual worlds. The objective of this research is to develop CSR concept through elaboration of divine values based on liberation theology. Liberation theology presents three main principles, namely, 1) Equitable distribution of wealth, 2) Managing earth as mandate of creation, and 3) Fulfilling basic human rights. The principle is taken as the basis to arrange the deliberative CSR concept that is able to promote a civil society. This research employed a qualitative approach with critical paradigm to interpret the phenomena and reconstruct CSR concept. The results of this research are: 1) The concept of tazkiah or soul purification in economic case, that is purifying human by spending their wealth in the way of Allah; 2) The concept of justice, as the basis to settle poverty issue; 3) Natural balance as the basis of utilizing natural resources; 4) Social welfare, which is the Prophet’s revolutionary mission through liberating human from ignorance, oppression, slavery, and poverty. The implication is that deliberative CSR liberates CSR from materialism’s capitalistic worldview. Deliberative CSR makes entity perform CSR beyond the obligation; which is as human necessity to actualize their duties as God’s representative on earth as the consequence of devotion to Allah SWT